2009
DOI: 10.1007/s12403-008-0002-3
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater Arsenic Contamination, Its Health Effects and Approach for Mitigation in West Bengal, India and Bangladesh

Abstract: Since 1988, water samples from 140,150 tubewells were analyzed for arsenic (As) in all 19 districts of West Bengal. In 9 districts, As has been found above the national standard (50 µg/L) and in 5 districts, between 10 and 50 µg/L. From Bangladesh, 50,515 tube-well water samples were analyzed from all 64 districts. Arsenic was present above 10 µg/L in 60 districts and in 50 districts, above 50 µg/L. Other than urine As speciation, 39,000 biological samples were analyzed from both patients and non-patients, 83%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(37 citation statements)
references
References 78 publications
(96 reference statements)
0
36
0
1
Order By: Relevance
“…The surfaces of ICS, IMCS, and MCS are positively charged below pH pzc 25 (Table 2). From the simulation of the aqueous speciation of phosphate by MINEQL+ software, phosphate is mostly present as a neutral species (H 3 PO 4 , pK a1 = 2.1) at low pH (2.1 ± 0.5), while it is present as negative ions such as H 2 PO 4 − and HPO 4 2− (pK a2 = 7.2 and pK a3 = 12.3, respectively) between pH 3 and 10. Phosphate is essentially fully deprotonated (PO 4 3− ) above pH 12.3.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The surfaces of ICS, IMCS, and MCS are positively charged below pH pzc 25 (Table 2). From the simulation of the aqueous speciation of phosphate by MINEQL+ software, phosphate is mostly present as a neutral species (H 3 PO 4 , pK a1 = 2.1) at low pH (2.1 ± 0.5), while it is present as negative ions such as H 2 PO 4 − and HPO 4 2− (pK a2 = 7.2 and pK a3 = 12.3, respectively) between pH 3 and 10. Phosphate is essentially fully deprotonated (PO 4 3− ) above pH 12.3.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In the presence of PO 4 3− , about a 50% reduction in arsenic removal was observed. Because PO 4 3− and AsO 4 3− have similar chemical structures, these two species might be in strong competition to occupy the finite number of adsorption sites on IMCS(7:3). A similar inhibition effect was reported for arsenic adsorption onto iron hydroxides.…”
Section: Removal Of As(iii) By Ics Mcs and Imcs In A Batchmentioning
confidence: 99%
“…[4][5][6][7][8][9][10] Therefore, the Environmental Protection Agency (EPA) lowered the maximum concentration level of arsenic in water systems from 50 to 10 µg/L. In addition, As(III) is more toxic and difficult to treat than As(V) species.…”
Section: )mentioning
confidence: 99%
“…But whatever be the approach, for success at field level, awareness among the people and their wholehearted participation is need (Das et al, 2009). …”
Section: Stretch Of Arsenic Pollution In West Bengalmentioning
confidence: 99%
“…Even now, many who are drinking arsenic-contaminated water are not even aware of this fact and its consequences (Das et al, 2009). Researchers at the School of Environmental Studies (SOES), Jadavpur University, India, have observed from their last 18 years' field experience in West Bengal, arsenic-affected people have also been facing serious social problems.…”
mentioning
confidence: 99%